A taxonomic revision of the genus Zyzzyzus Stechow, 1921 (Cnidaria: Hydrozoa: Tubulariidae) - Campos, Carlos J.a.; Marques, Antonio C.; Migotto, Alvaro E. (Zootaxa, 2007)
The hydrozoan genus Zyzzyzus is revised based on reexaminations of all available type specimens and on additional material. The taxon includes four valid species: Zyzzyzus spongicolus (von Lendenfeld, 1884), from the eastern Indian and southwest Pacific oceans; the type species, Z. warreni Calder, 1988, from the Atlantic, western Indian, and western Pacific oceans; and Z. floridanus Petersen, 1990 and Z. robustus Petersen, 1990, both from the northwest Atlantic. Although type specimens of Z. calderi Petersen, 1990 could not be located, it has been assigned here to the synonymy of Z. warreni because of similarities between the two in nematocyst dimensions, in number and structure of endodermal canals, and in external morphology of the hydrocaulus and hydrorhiza. A sixth nominal species (Corymorpha iyoensis Yamada, 1958) has on one occasion been assigned to the genus, but detailed studies of the type material are needed to resolve its taxonomic affinities.